Digestion of whey peptide induces antioxidant and anti-inflammatory bioactivity on glial cells: Sequences identification and structural activity analysis - Galland, Fabiana; de Espindola, Juliana Santos; Sacilotto, Eduarda Spagnol; Almeida, Lilian Gabriely V.C.; Morari, Joseane; Velloso, Lício Augusto; dos Santos, Lucilene Delazari [UNESP]; Rossini, Bruno Cesar [UNESP]; Bertoldo Pacheco, Maria Teresa (Elsevier, 2024)
Whey derived peptides have shown potential activity improving brain function in pathological condition. However, there is little information about their mechanism of action on glial cells, which have important immune functions in brain. Astrocytes and microglia are essential in inflammatory and oxidative defense that take place in neurodegenerative disease. In this work we evaluate antioxidant and anti-inflammatory potential bioactivity of whey peptide in glial cells. Peptides were formed during simulated gastrointestinal digestion (Infogest protocol), and low molecular weight (<5kDA) peptides (WPHf) attenuated reactive oxygen species (ROS) production induced by hydrogen peroxide stimulus in both cells in dose-dependent manner. WPHf induced an increase in the antioxidant glutathione (GSH) content and prevented GSH reduction induced by lipopolysaccharides (LPS) stimulus in astrocytes cells in a cell specific form. An increase in cytokine mRNA expression (TNFα and IL6) and nitric oxide secretion induced by LPS was attenuated by WPHf pre-treatment in both cells. The inflammatory pathway was dependent on NFκB activation. Bioactive peptide ranking analysis showed positive correlation with hydrophobicity and negative correlation with high molecular weights. The sequence identification revealed 19 peptides cross-referred with bioactive database. Whey peptides were rich in leucine, valine and tyrosine in the C-terminal region and lysine in the N-terminal region. The anti-inflammatory and antioxidant potential of whey peptides were assessed in glia cells and its mechanisms of action were related, such as modulation of antioxidant enzymes and anti-inflammatory pathways. Features of the peptide structure, such as molecular size, hydrophobicity and types of amino acids present in the terminal region are associated to bioactivity.
Keywords: Anti-inflammation; Antioxidant; Simulated digestion; Whey peptide